2016
DOI: 10.1038/srep31795
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis of Buffalo Oocytes Matured in vitro Using iTRAQ Technique

Abstract: To investigate the protein profiling of buffalo oocytes at the germinal vesicle (GV) stage and metaphase II (MII) stage, an iTRAQ-based strategy was applied. A total of 3,763 proteins were identified, which representing the largest buffalo oocytes proteome dataset to date. Among these proteins identified, 173 proteins were differentially expressed in GV oocytes and competent MII oocytes, and 146 proteins were differentially abundant in competent and incompetent matured oocytes. Functional and KEGG pathway anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 57 publications
(66 reference statements)
0
17
0
Order By: Relevance
“…Li et al explored the expression profiles of mRNAs, lncRNAs, and circRNAs in male and female mouse germline stem cells by high‐throughput sequencing . Regarding proteomics of female germ cells, Chen et al analysed buffalo oocytes matured in vitro by using the iTRAQ technique . Virant‐Klun et al identified maturation‐specific proteins in human oocytes by single‐cell proteomics .…”
Section: Introductionmentioning
confidence: 99%
“…Li et al explored the expression profiles of mRNAs, lncRNAs, and circRNAs in male and female mouse germline stem cells by high‐throughput sequencing . Regarding proteomics of female germ cells, Chen et al analysed buffalo oocytes matured in vitro by using the iTRAQ technique . Virant‐Klun et al identified maturation‐specific proteins in human oocytes by single‐cell proteomics .…”
Section: Introductionmentioning
confidence: 99%
“…Competence development of oocytes is primarily dependent on the biochemical and structural transformations that occur in the cytoplasm (Ferreira et al, 2009;Khan et al, 2016). These transformations, involved in maturation, are highly intricate processes involving several simultaneous events, such as protein syntheses, molecular modifications, migration and reorganization of organelles in the cytoplasm (Chen et al, 2016;Khan et al, 2016). These changes in the oocyte cytoplasm will be discussed in more detail in the following sections.…”
Section: Cytoplasmic Maturationmentioning
confidence: 99%
“…However, gene transcription ceases before ovulation, so the oocyte, zygote, and embryo (Figure 3), with less than 16 blastomeres (bovine), are dependent on the pool of mRNAs and proteins accumulated during the period of growth and maturation (Meirelles et al, 2004;Salilew-Wondim et al, 2018). Oocytes depend on the synthesis and activation of a variety of proteins so they can enter and continue the process of oocyte maturation (Soeda et al, 2013;Chen et al, 2016).…”
Section: Molecular Changesmentioning
confidence: 99%
“…The iTRAQ method is a highly sensitive proteomic platform, which is characterized by high proteome coverage and labeling efficiency, and has no side effects on analytical or biochemical properties of the labeled proteins or peptides [11,12]. However, the iTRAQ technique is proved to be more suitable for initial biomarkers discovery, and the results would require validation through a large-scale screening [13,14]. In our study, we presented details of proteome variation in the different ESCC tumor tissues based on an iTRAQ with reversedphase liquid chromatography-mass spectrometry (RPLC-MS) approach, and further validated the observations by tissue microarray (TMA) based on large samples immunohistochemistry.…”
Section: Introductionmentioning
confidence: 99%